Feed Efficiency and Growth Modeling of KUB Chicken: A Comparison Between Commercial and Alternative Feeds - Oktariansyah, Yadi; Cahyani, Riski; Masito, Masito (Mahesa Research Center, 2025)
Feed costs constitute a major expense in poultry production, emphasizing the need for efficient feeding strategies among smallholder farmers. The Ayam Kampung Unggul Balitbangtan (KUB) chicken is a promising native breed, yet limited research integrates feed efficiency with growth prediction modeling. This study evaluated commercial and alternative feed types while developing growth models. Twenty-five KUB chickens ( 7 days old) were assigned to five dietary treatments: 100% commercial feed, 100% corn, 100% rice bran, 50% commercial + 50% corn, and 50% commercial + 50% rice bran, arranged in a completely randomized design with five replications. Body weight and feed conversion ratio (FCR) were recorded weekly for four weeks and analyzed using ANOVA. Nonlinear models (Exponential, Gompertz, Logistic) were applied for growth prediction. Feed type (F = 14.30, p 0.001), week (F = 292.68, p 0.001), and their interaction (F = 3.53, p 0.01) significantly affected body weight. The mixed diet of 50% commercial feed and 50% corn produced the highest final weight (228.8 g), while corn and rice bran diets resulted in lower growth. Logistic models best described balanced diets, whereas Exponential models reflected nutrient-limited growth, providing predictive insights aimed at enhancing feed strategies for smallholder farmers.